Alkaline DMSO superoxide and radical scavenging, cupric reducing antioxidant capacity (CUPRAC) and polyphenol contents of aqueous and methanol extract from Achilllea santolinoides L. aerial parts - Soulaf Mehlous; Smain Amira; Fatima Benchikh; Hassiba Benabdallah; Walid Mamache; Chawki Bensouici; Hocine Laouer; Karima Loucif (Turkish Journal of Agriculture: Food Science and Technology)
The genus Achillea (Yarrow)is one of the most important medicinal plants. Nowadays, different medicinal functions of yarrow such as spasmolytic, choleretic, treatment of wounds and anti-inflammatory activities, make it as an important medicinal plant. The purpose of this study was to determine the antioxidant activity of aqueous (AAE) and methanol (AME) extracts from the plant Achillea santolinoides L. (A. santolinoides L.) aerial parts in vitro. Quantitative evaluation of polyphenols, flavonoids and tannins were determined using Folin-Ciocalteu reagent, aluminum chloride (AlCl3) and Bate Smith methods, respectively. Antioxidant activity was carried out using ABTS radical scavenging, alkaline DMSO superoxide radical scavenging and cupric reducing antioxidant capacity (CUPRAC). The obtained results showed that the highest content in total phenolic, flavonoids and tannins was found in the AME with values of 210.78±0.001 µg GAE/mg Dw, 21.18±0.025 µg QE/mg DW and198.73±0.014µg TAE/mg DW, respectively. For the in vitro antioxidant activity, AME had the strongest ABTS and DMSO alkaline radical scavenging activity (IC50= 6.74±0.16 µg/mL and 15.13±0.92 µg/mL, respectively) and the CUPRAC reducing with A0.50 of 76.56±2.35 µg/mL. The results of the present study confirm the use of the genus Achillea in the treatment of various diseases as a powerful antioxidant.